Toward the Implementation of Evidence-Based Interventions for Youth With Autism Spectrum Disorders in Schools and Community Agencies. Issue 1 (January 2015) - Wood, Jeffrey J.; McLeod, Bryce D.; Klebanoff, Sami; Brookman-Frazee, Lauren
Abstract Evidence-based interventions (EBIs) for youth with autism spectrum disorders (ASD) are rarely found in community settings where most youth with ASD receive services. Implementation research designed to help bridge this gap is needed. However, efforts to implement EBIs in community settings face a number of barriers. The main purpose of this article is to illustrate how making EBIs more flexible and integrative may help improve their utility and may increase their uptake by stakeholders in community mental health and school settings. We conclude with an example of a modular, stepped-care program that might help bridge the science-practice gap in the ASD field by combining elements of a number of existing EBIs into a single, flexible intervention.